Estimated length of soybean phenological stages - Rockenbach, Ana Paula; Caron, Braulio Otomar; Souza, Velci Queiroz de; Elli, Elvis Felipe; Oliveira, Douglas Machado de; Monteiro, Gean Charles [UNESP] (Univ Estadual Londrina, 2016)
The use of modeling is a trend for agronomic science that aims to detect factors that could limit the growing practices and influence the potential yield of some crops. The objective of this study was to calculate the accumulated thermal time and estimate the phenological stages length of three soybean cultivars in two crop years, using agronomic models associated to meteorological variables. Two experiments were conducted in a field at the Agroclimatology Laboratory (LAGRO) of the Federal University of Santa Maria/UFSM, campus of Frederico Westphalen/RS, Brazil during the 2012/2013 and 2013/2014 crop years. A randomized block in a factorial scheme 6x3 with six spatial arrangements (45, crossed, 20, 20x40, 20x60 and 20x80 cm) and three cultivars with different cycles and growth habits (BMX Ativa RR/determinate, BMX Turbo RR/indeterminate and BMX Potncia RR/indeterminate) with three replications were used for the experimental design. Sowing was held on 11/28/2012 and 12/02/2013. The assessed phenological stages were sowing-emergence; emergence-final vegetative; final vegetative-full bloom; full bloom-physiological maturity. The duration of each stage was related to meteorological parameters: maximum temperature, minimum temperature, average temperature, rainfall, solar radiation, and thermal time. Air temperature influences soybean growth and development. The accumulated thermal time varies between years and among cultivars, and it is the main contributor to the estimated duration of the phenological stages.
Keywords: Weather elements; Glycine max L; Merrill; Agronomic models; Thermal time; Temperature